Effect of Salinity, Alkalinity and Mulch on Thee Ghowth in Dry Hegion - Gupta, G N; Prasad, K G; Mohan, S (Annals of Arid Zone, 2016)
Pot culture and field experiments were conducted to investigate the influence of salinity, alkalinity and mulching on the growth of various tree species. In pot culture study salinity levels of 0, 2.5, 5, 10 and 15 dS/m and alkalinity levels as control (pH 8.60 of loamy sand, 7.29 of clayJoam and 8.45 of clay soil), 9.3 and 10.3 pH were simulated in three soils. It was observed that Acacia nilotica and Eucalyptus camaldulensis grew with less than 50% growth reduction upto the salinity of 5 dS/m and pH of 10.3 (in sandy soil) and 9.3 (in clay soil). Acacia nilotica tolerated salinity as high as 10 dS/m (with dry matter yield being one third of the control). Casuarina equisetifolia tolerated salinity upto 2.5 dS/m and alkalinity upto 9.3 pH (only in loamy sand soil). Ceiba pelntaldra and Acacia auriculaeformis were sensitive to both salinity and alkalinity. In field experiment, salinity (0, 1.5, 3 and 6 dS/m) and alkalinity (control, 8.9 and 9.7 pH) were simulated to a depth of 1 metre, and treatments of no mulching and coirpith mulching were super imposed. At 6 dS/m salinity, reduction in plant growth was 23 per cent in E. camaldulel/sis, 41% in C. equisetifolia and 50% in T. indica. At 9.7 pH growth of C. equisetifolia reduced by 15 per cent, E. camaldulensis by 58 per cent and T. indica wilted completely. Coirpith mulching improved the plant growth appreciably on saline soils. Mulching enhanced soil moisture content and lowered the soil temperature.